Magnetic crustal features in the Vinchina basin. (July 2017) - Weidmann, Cecilia; Ariza, Juan Pablo; Sánchez, Marcos; Gimenez, Mario; Christiansen, Rodolfo
Abstract: This research based on geological and geophysical data encompasses the South Central Andes region between 28 S and 31 S. We observed a region of high-magnetic susceptibility linked to sources located beneath the Vinchina basin through anomaly calculations and enhancing techniques using aerial and terrestrial magnetic data. The Curie Point Depth (CPD) obtained from the magnetic anomalies reflects a cold crust of approximately 50 km thick with CPD values of up to 40 km. These results are consistent with those obtained by other authors by means of mineral, isotopic, and thermo-chronological analysis in clay levels of the Vinchina basin sedimentary infill. Highlights: The depth of Curie point obtained from the magnetic anomalies. The magnetic anomaly map shows regions with positive values well-differentiated. An important positive anomaly can be observed; this anomaly surpasses the Vinchina basin, with the reduction to the pole. In the north the Tilt signal is disposed in W-E, changing it abruptly which can be due to the entrance of Copiapó ridge.